PERBANDINGAN PENINGKATAN BERAT BADAN ANAK MENCIT YANG DIINDUKSI OLEH PEMBERIAN INFUS DAUN PEPAYA DAN DAUN KATU - IB. Rai Pidada (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
A comparative study of increasing on body weight of mice ,s offsprings caused by leaf of papaya (Carica pepaya L.) and katu (Sauropus androgynus (L). Merr) were carried out under laboratory conditions. The study was designed using totally 50 mice post partum (PP) which devided into five groups of treatment consistent 10 females mice post partum of each group. The groups were: The control group, group gave orally in 0.5 ml aquadest, 10%/0.5 ml, and 20%/0.5 ml leaf infuse of papaya and 10%/0.5 ml and 20%/0.5 ml leaf infuse of katu respectively. The treatment were started on day 3rd to 16th of lactation period. The sample were observed on day 4th, 6th , 8th, 10th, 12nd, 14th, and 16th of lactation period. The data were analyzed by ANOVA and LSD test (α = 0.05). The result of study showed that the increasing of body weight of offsprings were significantly different amongs of five groups. Between the control groups and katu groups was not occurred significantly different. The conclusion of this study is papaya groups more right than katu groups to induce an increasing on body weight of mice,s offsprings.